Resilience Across the Life Course for Women Experiencing Intimate Partner Violence - Davidson, Cara A. (Violence against women, 2025)
This study employed a life course perspective to explore the resilience of Canadian women of various ages who had experienced intimate partner violence (IPV). Interpretive description was used to analyze 22 in-depth, semi-structured interview transcripts with women who ranged in age from >19 to 60+ years. Results revealed that developmental age affected service accessibility and effectiveness, historical age shaped abuse normalization, and social age presented barriers and facilitators to women's resilience. This study highlighted the central role of resilience for women of all ages who have experienced IPV and emphasized the need for accessible, effective, and supportive services.